(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Mahrus H, Idrus AA, Zulkifli L. 2022. Molecular phylogeny of anchovy (Clupeiformes: Clupeidae) from southern waters of Lombok using mitochondrial DNA CO1 gene sequences. Biodiversitas 23: 2433-2443. This study aimed to identify anchovy samples genetically and evaluate their phylogenetic relationship to anchovies using the CO1 genetics markers. Fragment amplification of COI gene anchovy used a pair of COI commercially available primer with a length amplicon of about 693 base pairs (bp), coding for 231 amino acids successfully. The reconstruction of the phylogenetic tree with the neighbor-joining (NJ) method using Kimura 2 Parameters (K2P) by employing a bootstrap of 1000 replications. The genetic distance analysis between 19 fishes species in different families and 13 species in the genera Spartelloides acceded from NCBI indicated the closest distance between anchovy samples from the southern waters of Lombok and Spratelloides delicatulus from Australia is 0.02. The comparisons results of homology with the NCBI and the BOLD database show the anchovy sample has similarities to the CO1 sequences of S. delicatulus with a similar of 99%. The results of the phylogenetic tree analysis showed that the anchovy samples from the southern waters of Lombok were in the same clade as S. delicatulus from Australia. The study concluded a fish sample of anchovy from the southerly waters of Lombok was a closed related species to S. delicatulus.